Analisis Laporan Keuangan sebagai Alat untuk Menilai Kinerja Keuangan Perusahaan pada PT. Pembangunan Perumahan (Persero) Tbk (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the effect of company size, profitability, investment, and free cash flow on dividend payment policy in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2021 period. The research method used is a quantitative approach with multiple linear regression analysis techniques. The sample in this study consisted of 25 manufacturing companies selected through a purposive sampling method based on certain criteria. The results of the study indicate that company size, investment, and free cash flow have a positive and significant effect on dividend payment policy. Meanwhile, profitability has a negative and significant effect on dividend payment policy. This finding indicates that dividend payment policy is more influenced by the financial and liquidity aspects of the company, not solely by the level of profitability. This study implies that companies need to consider internal factors such as size and cash flow in formulating dividend policies, especially in uncertain economic conditions.